Developing OSCE for Pharmacy Students in The Pandemic Era - Nurul Maziyyah; Annisa Krisridwany (Jurnal Farmasi Indonesia, 2020)
The COVID -19 pandemic has affected many aspects of life, one of which is in the field of education. Transformation toward various e-learning process has been conducted in order to prevent transmission of the disease caused by massive gathering. Obstacles appear when trying to deliver and assess practical skills which are usually done face to face with the teachers or instructors. These obstacles are also seen in pharmacy schools where skills such as patient counselling, compounding and dispensing, etc. are important competencies for the students to achieve. In order to overcome these obstacles, we developed a method for conducting the objective structured clinical examination (OSCE) through online process. This study was aimed to evaluate the new online OSCE method for pharmacy students to be conducted in the pandemic era. The evaluation of online OSCE trial was conducted using a simple Google form-based questionnaire which evaluated the platform used, the process of online OSCE and the instruction understandings. Respondents consisted of 52 examinees from the students of Pharmacist Profession Program UMY and 15 examiners from the lecturers or assistants who participated in the online OSCE trial held in June 2020. Data was analyzed descriptively to give a comprehensive picture on respondents’ perception towards the new method. The result showed that 78.8% examinees and 73.3% examiner agreed that the platform was easy to use, 65.4% examinees and 100% examiner agreed that the whole process of the exam was easy to understand, only 15.4% examinees and 26.7% examiner agreed that the time was sufficient, 73.1% examinees and 100% examiner agreed that the instructions of each station was clear. It can be concluded from the study that online OSCE method was feasible to be conducted during pandemic, particularly, for clinical pharmacy skills. Adjustment should be done to ensure that the time allocation for each station is adequate.